Peningkatan Keterlibatan Masyarakat dan Nilai Ekonomi Limbah Rumah Tangga dan Pasar melalui Budidaya Maggot Black Soldier Fly - Purwono Purwono; Ardhi Ristiawan; Annida Unnatiq Ulya; Ronnawan Juniatmoko; Septin Puji Astuti (Jurnal Pengabdian Pada Masyarakat, 2021)
INCREASING COMMUNTY INVOLVEMENT AND ECONOMIC VALUE OF HOUSEHOLD AND MARKET SOLID WASTE THROUGH CULTIVATING BLACK SOLDIER FLY MAGGOTS. The Klaten Regency area has at least more than 80 traditional markets owned by villages and local governments spread across a number of locations. Every market produces organic waste. About 60% of waste is generated from traders and 40% from residents around the market. Besides that, the community also produces large amounts of household solid waste. This service activity aims to increase the economic value of waste and the involvement of the community in Gempol Village, Karanganom District, Klaten Regency through the cultivation of black soldier fly (BSF). The service method starts with team formation, formulation of goals and outcome, identification of stakeholders, data collection and needs analysis, determination of priority problem solutions, preparation, implementation, mentoring, review and evaluation, determining new needs and targets. The result shows that Gempol village is ideal when managing household and market waste through BSF maggot cultivation. Through BSF maggot cultivation, household and markets solid waste are able to add economic value in a period of 7 days to 15 days. Dry maggot has a high selling value ranging between Rp. 95.000 / kg. Maggot derivative products such as fish feed, poultry feed, fishing bait range from Rp. 325.000/kg. The first outcome from this service activity was the enthusiasm of the community to be involved in managing household and market solid waste. The second outcome was stakeholder involvement, in this case the Environment and Forestry Service (DLHK) of Klaten Regency. The third outcome is opportunities for cooperation between participants (especially farmer groups) and universities. Participants hope that there will be sustainable activities, mentoring, and collaboration with other parties.